(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Fine Needle Aspiration Cytology (FNAC) is a well-practiced simple, safe, rapid, cost effective diagnostic procedure which has been appreciated by clinicians and pathologists worldwide in recent times. The aim of this study is to evaluate the diagnostic accuracy of Fine needle aspiration in head and neck lesions and its correlation with histopathological examination. Materials and methods: This cross sectional descriptive study carried out in the Department of Pathology, Chittagong Medical College, Chattogram, Bangladesh over a period of one year from 1 st January 2017 to 31 th December 2017 on 202 consecutive cases who fulfilled the criteria of this study. FNAC were performed in each case. FNAC association with histopathology in available specimen were assessed in selected cases, the histopathological sections were stained with H&E, ZN stains and immunohistochemical stains, where applicable. Results: The mean age of the patients was 33.71± 16.04 with female predominance 135 (66.8%). It was observed that the incidence of thyroid lesion was the highest followed by lymph node lesion. The overall sensitivity, specificity, accuracy were 92.16%, 85% and 76.06% respectively. Conclusions: The study found that FNAC is a quick, inexpensive technique to diagnose different types of head and neck swellings. It can be repeated easily if required and it may also help the surgeon to select, guide and modify surgical planning in patients requiring surgery. JCMCTA 2023 ; 34 (2) : 56-61